+0  
 
0
124
3
avatar+55 

\((x+y)^2 = x^2 + y^2\)

 Jun 30, 2021
edited by BigBoiChungus  Jun 30, 2021
 #1
avatar+121047 
+3

(x +  y)^2   =   x^2  +  y^2

 

x^2  +  2xy  +  y^2 =  x^2  + y^2                   (subtract   x^2, y^2   from both sides)

 

2xy     =  0

 

xy =  0                which  implies  that  x =  0   or y =  0     or  both  =   0

 

cool cool cool

 Jun 30, 2021
 #2
avatar+55 
+1

Thank you!

BigBoiChungus  Jun 30, 2021
 #3
avatar+55 
+1

Oh, i've also had this burning question, why do all your answers have hundreds of spaces XD

BigBoiChungus  Jun 30, 2021

22 Online Users

avatar